2016
DOI: 10.1186/s40064-016-3786-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of microRNA-124a and microRNA-30d with clinicopathological features of breast cancer patients with type 2 diabetes mellitus

Abstract: This study intends to investigate the correlations of miR-124a and miR-30d with clinicopathological features of breast cancer (BC) patients with type 2 diabetes mellitus (T2DM). A total of 72 BC patients with T2DM (diabetic group) and 144 BC patients without T2DM (non-diabetic group) were enrolled in this study. Blood glucose was detected by glucose oxidase methods. Glycosylated hemoglobin (HbA1c) was measured by high performance liquid chromatography. Fasting insulin (FIns) was measured by chemiluminescent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…However, Naohito et al found that miR‐30d could increase prostate cancer cell proliferation and invasion and act as a novel prognostic maker of prostate cancer. Moreover, there is convincing evidence that miR‐30d serves as a novel prognostic biomarker in breast cancer in patients with type 2 diabetes mellitus . Consistent these results, we found that miR‐30d was increased in breast cancer cell lines and miR‐30d overexpression promotes cell growth and metastasis whilst inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, Naohito et al found that miR‐30d could increase prostate cancer cell proliferation and invasion and act as a novel prognostic maker of prostate cancer. Moreover, there is convincing evidence that miR‐30d serves as a novel prognostic biomarker in breast cancer in patients with type 2 diabetes mellitus . Consistent these results, we found that miR‐30d was increased in breast cancer cell lines and miR‐30d overexpression promotes cell growth and metastasis whilst inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence indicated that the expression of miR-30d was increased in multiple types of cancers, 27 including breast cancer with type 2 diabetes mellitus. 14,15 Firstly, we found that miR-30d expression was markedly increased in breast cancer cell lines BT474, MDA-MB-231, HCC197, and MDA-MB-468 compared with the control normal cells MCF-10A ( Figure 1). The increase was most obvious in MDA-MB-231 cells and was poorly increased in BT474 cells.…”
Section: Mir-30d Is Increased In Breast Cancer Cell Linesmentioning
confidence: 98%
See 1 more Smart Citation
“…SOCS3 expression arrested IL‐1‐induced apoptosis in the primary pancreatic islets in both mice and rats, while SOCS3 knockout mice have been discovered to be resistant to streptozotocin‐induced type 1 diabetes mellitus (T1DM) (Rezende, Santos, Carneiro, & Boschero, ). Han et al demonstrated among patients with high level of glucose or with diabetes, that the expressions of miR‐30d up‐regulated levels of glucose to increase the expression rate of insulin gene, while the inhibition of miR‐30d decreased glucose‐stimulated insulin gene transcription, indicating miR‐30d could potentially serve as a vital negative regulator of insulin gene expression (Han et al, ). Additionaly, SOCS3 restoration by means of a demethylating agent in methylated pancreatic cells was found to markedly suppress cell proliferation and induce apoptosis of cells such as pancreatic cancer (PaC) (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore miR‐30d expression has been shown to be significantly higher in high‐glucose‐treated cardiomyocytes and streptozotocin (STZ)‐induced rats with DM (Li et al, ). Additionally, miR‐30d has been reported to play a vital role in influencing the functions of β‐cells that are impaired via pro‐inflammatory cytokines and in the activation of glucose‐induced insulin gene transcription, which serves as an important target for diabetes intervention (Han, Cao, Wang, Dong, & Chen, ). The suppressors of cytokine signaling (SOCS) protein family consist of SOCS1‐7 as well as eight other members including cytokine‐induced STAT inhibitor (CIS) (Dong et al, ), operates as a negative regulatory factor that mainly inhibits the differentiation, proliferation, and induction of apoptosis by suppressing the the Janus kinase (JAK)‐signal transducer and activator of transcription (STAT) signaling pathway (Liu, Li, Dong, et al, ).…”
Section: Introductionmentioning
confidence: 99%